Superior quality chemically reduced graphene oxide for high performance EMI shielding materials. Issue 35 (12th August 2022) - Sadek, Ramy; Sharawi, Mohammad S.; Dubois, Charles; Tantawy, Hesham; Chaouki, Jamal
Abstract : The developed two-step protocol offers a superior reduced graphene oxide TCRGOL quality (7 layers), and its SET was 94 dB over the X-band. Abstract : The chemical reduction process of graphene oxide combined with a mild and controllable thermal treatment under vacuum at 200 °C for 4 hours provided a cost-effective, scalable, and high-yield route for Reduced Graphene Oxide (RGO) industrial production and became a potential candidate for producing electromagnetic interference (EMI) shielding. We investigated graphite, and RGO using l -ascorbic acid and Sodium borohydride before and after thermal treatment by carefully evaluating the chemical and morphological structures. The thermally treated l -ascorbic Acid reduction route (TCRGOL) conductivity was 2.14 × 10 3 S m −1 and total shielding efficiency (SET) based on mass loadings per area of shielding was 94 dB with about one-tenth less graphite weight and surpassing other graphene reduction mechanisms in the frequency range of 8.2–12.4 GHz, i.e., X-band, at room temperature while being tested using the waveguide line technique. The developed treatment represents valuable progress in the path to chemical reduction using a safe reducing agent and offering superior quality RGO rarely achieved with the top-down technique, providing a high EMI shielding performance.